Method for reinforcing slag cement-based recycled mortar
Through the phased stirring process, the production process of slag cement-based recycled mortar was optimized, and the problem of insufficient strength of recycled mortar in the existing technology was solved, which significantly improved the compressive and flexural strength of the mortar and enhanced its application potential in the field of building materials. .
Patent Information
- Application Number
- CN202411753088.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-18
AI Technical Summary
When using regenerated mortar with construction waste, the mixing process is single, making it difficult to effectively improve the strength and durability of the regenerated mortar.
The regenerated sand is divided into two parts according to the particle size, large particle size and small particle size, and cement, slag and water reducing agent are gradually added through multiple stirring steps to form a uniform regenerated mortar mixture.
The compressive strength and flexural strength of slag cement-based recycled mortar are significantly improved, the overall performance and microstructure of the mortar are improved, and its reliability in practical applications is enhanced.
Smart Images

Figure CN119462203A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for strengthening slag cement-based recycled mortar. Background Art
[0002] Construction waste contains a large amount of block materials such as concrete, sintered bricks, autoclaved bricks and ceramics. If it is only disposed of by simple landfill, it will be a huge waste of resources. On the contrary, by reusing these materials as aggregates after proper treatment, it can not only save precious natural aggregate resources and protect the ecological environment, but also effectively solve the problems of stacking, land occupation and environmental pollution caused by construction waste.
[0003] At present, there are more and more studies on the recycling of blocky construction waste at home and abroad. Construction waste processed by crushers can be divided into recycled coarse aggregate, recycled sand and recycled micro powder according to the particle size. Among them, recycled sand accounts for about 30% of the total construction waste, while recycled micro powder accounts for about 15%. Given that recycled sand and recycled micro powder account for nearly half of the total amount, in-depth research on their properties is of great significance to promote the resource utilization of construction waste.
[0004] However, existing studies have shown that the strength of recycled aggregate concrete is affected by many factors, including the physical and mechanical properties of recycled sand (such as bulk density, apparent density, crushing index, water absorption and impurity content, etc.), the crushing and processing methods of recycled aggregates, as well as the damage accumulation inside the aggregates, microcracks and the bonding strength of the new and old interfaces in recycled concrete, etc. These factors not only determine the strength of concrete, but also have an important impact on its durability.
[0005] The microstructure of recycled concrete becomes more complex than that of ordinary concrete due to the addition of recycled aggregates. This complex microstructure brings challenges to the analysis of the durability mechanism of recycled aggregate concrete, resulting in its relatively limited application in practical engineering.
[0006] Chinese patent CN118878266A discloses a recycled mortar made from crushed waste FRP sand-filled pipes and a preparation method thereof, which uses crushed waste FRP sand-filled pipes to recycle fine aggregate to replace part of the river sand to prepare the recycled mortar made from crushed waste FRP sand-filled pipes, focusing on the recycling and reuse of waste FRP sand-filled pipes. The mixing process in the preparation method is single, which is only for the purpose of achieving uniform mixing, and does not involve improving the strength of the recycled mortar by optimizing the mixing process. Chinese patent CN118619630A discloses a low-carbon recycled sand concrete and a preparation method thereof, which uses various materials (activation liquid, auxiliary powder, mixed acid solution), calcination process, CO 2 Carbonation curing and other methods are used to improve the performance of recycled sand concrete. This patent uses a large number of materials, and the production process of recycled sand concrete is complex and the cost is high. Summary of the invention
[0007] In view of the current challenges in the treatment and resource utilization of construction waste, the present invention proposes a method for changing the mixing process to strengthen slag cement-based recycled mortar, aiming to significantly improve the performance of slag cement-based recycled mortar.
[0008] The technical solution adopted by the present invention is as follows: A method for strengthening slag cement-based recycled mortar, comprising the following steps: (I) Fine grading: The regenerated sand is divided into two parts according to the particle size: large particle size and small particle size, and the particle size cutoff point is set at 0.63-2.50 mm; (II) Stirring in stages: (1) Primary mixing: Mix large-size regenerated sand and water for 25 to 55 seconds; (2) Secondary stirring: Then add part of the slag and stir for 40 to 70 seconds; (3) Third mixing: Add cement and remaining slag and mix for 40 to 70 seconds; (4) Fourth mixing: add small-size regenerated sand, remaining water and water reducer, stir for 40 to 70 seconds to form a uniform regenerated mortar mixture, and cast the test block; Among them, the mass ratio of cement, slag, regenerated sand, water and water reducing agent is 0.1-0.9: 0.1-0.9: 2.0-4.0: 0.7-1.1: 0-0.0125.
[0009] Strengthening of the interface transition zone: The mixing process of the present invention effectively repairs the weak surface area by forming a slag coating layer on the surface of the large-size regenerated sand, strengthens the interface transition zone between the aggregate and the cement mortar, and thus improves the overall performance of the mortar.
[0010] Strengthening of slag cement-based paste: The mixing process of the present invention partially reduces the ratio of slag to cement in the slag cement composite cementitious material by step-by-step mixing, thereby increasing the degree of pozzolanic reaction of the slag cement paste.
[0011] Preferably, the particle size cutoff point is set at 0.63 mm.
[0012] Preferably, the particle size cutoff point is set at 1.25 mm.
[0013] Preferably, the first stirring time is 30 seconds, the second stirring time is 60 seconds, the third stirring time is 60 seconds, and the fourth stirring time is 60 seconds.
[0014] Preferably, the water reducing agent is a polycarboxylic acid type water reducing agent.
[0015] Preferably, the slag is added in batches, and the mass ratio of the slag added for the first time to the slag added for the second time is 1:0-6.
[0016] Preferably, the mass ratio of the water added for the first time to the water added for the second time is 1:1-4.
[0017] The present invention can wrap a layer of slag admixture on the surface of large-particle regenerated fine sand. The slag itself has a certain hydration activity, and the slag can be adsorbed into the pores on the surface of the wet regenerated sand, and react with the calcium hydroxide in the regenerated sand to generate hydrated calcium silicate. The products of the slag hydration reaction and the volcanic ash reaction can effectively fill the pores on the surface of the regenerated sand, reduce the porosity of the regenerated sand, improve its compactness, and achieve in-situ strengthening of the regenerated sand. At the same time, the slag on the surface of the regenerated sand can further react with the calcium hydroxide enriched at the interface of the regenerated sand-cement slurry, thereby significantly improving the microstructure of the transition zone of the regenerated mortar interface and improving the flexural and compressive strength of the regenerated mortar. In addition, when the slag content is high, by stirring the slag in parts, the slag content in the cement slurry can be reduced, the slag-cement ratio can be optimized, the microstructure of the cement slurry can be improved, and the slurry strength can be improved.
[0018] The process of the present invention is simple. By changing the stirring process, the strength of the regenerated sand, the regenerated sand-cement slurry interface and the cement slurry can be improved at the same time, thereby significantly improving the compressive strength of the slag cement-based regenerated mortar. Through the innovative steps and precise control of the present invention, not only the mechanical properties of the slag cement-based regenerated mortar are improved, but also an effective technical approach is provided for the resource utilization of construction waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the conventional mixing flow chart (NM); Figure 2 This is the stirring process flow chart (MTM) of the present invention. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0021] The cement in the examples of the present invention adopts PI42.5 grade standard cement produced in Fushun; The regenerated sand was provided by Tongxiang Tongde Wall Building Materials Co., Ltd. After a simple crushing process, the particle size was less than 9.5 mm and the fineness modulus was 2.9. The slag is S95 grade slag produced by Gongyi Longze Water Purification Material Co., Ltd.; The water reducing agent used is Melflux 4930F water reducing agent produced by BASF; The water used for mixing and curing slag cement-based recycled mortar is ordinary tap water.
[0022] The relevant indicators of regenerated sand are shown in Table 1.
[0023] Table 1 <![CDATA[Apparent density (kg / m 3 )]]> <![CDATA[Bulk density (kg / m 3 ).]]> Water absorption (%) Reclaimed sand 2380 1160 17.7 The specimens were made in the laboratory, with a size of 40 mm × 40 mm × 160 mm prisms. The specimens were mixed with materials in a forced mixer and compacted on a vibrating table. After 24 hours of demoulding, the specimens were cured under standard curing conditions for 28 days before the compressive strength test. The mechanical properties of slag cement-based recycled mortar were determined in accordance with the relevant provisions of the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021).
[0024] The process of preparing slag cement-based recycled mortar by conventional mixing method is as follows: Figure 1 As shown, the regenerated sand, cement and slag are stirred for 30 seconds to obtain a wet mixture, and then water and a water reducing agent are added and stirred for 90 seconds to obtain a fresh mortar.
[0025] Example 1 Reference Figure 2 A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: First, the regenerated sand is divided into two main parts according to the particle size: a large particle size part with a particle size greater than 0.63 mm and a small particle size part with a particle size less than 0.63 mm.
[0026] (II) Staged stirring process: (1) Primary mixing: Mix large-size regenerated sand and a corresponding amount of water (water m 1 ) Mix and stir for 30 seconds to obtain wet regenerated sand; (2) Secondary stirring: Then add part of the slag (slag m 1 ), stirring for 60 seconds; (3) Third mixing: Add cement and remaining slag (slag m 2 ), stirring for 60 seconds to obtain surface-coated slag regenerated sand; (4) Fourth stirring: Add small-size regenerated sand and remaining water (water m 2 ) and water reducing agent to obtain a wet mixture, which was stirred for 60 seconds to form a uniform recycled mortar mixture (fresh mortar) and cast test blocks.
[0027] Material ratio: In this embodiment, the material ratio is strictly controlled to ensure the best performance. The specific ratio is as follows:
[0028] Cement: 191 kg / m³ Slag: 191 kg / m³ (38 kg / m³ in the first part, 153 kg / m³ in the second part) Regenerated sand: 1147 kg / m³ (large particle size 803 kg / m³, small particle size 344 kg / m³) Water: 382 kg / m³ (125 kg / m³ in the first part, 257 kg / m³ in the second part) Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 5.31 MPa and 4.94 MPa, respectively, and the compressive strength is 23.66 MPa and 17.50 MPa, respectively. The results show that the mortar prepared by the method of the present invention is 7.49% higher in flexural strength and 35.20% higher in compressive strength than the conventional method.
[0029] Conclusion: Example 1 demonstrates the effectiveness of the mixing process of the present invention in improving the performance of slag cement-based recycled mortar, and verifies its application potential in the field of building materials.
[0030] Example 2 Reference Figure 2 A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: First, the reclaimed sand is divided into two main parts according to the particle size: a large particle size part larger than 0.63 mm and a small particle size part smaller than 0.63 mm.
[0031] (II) Staged stirring process: (1) Primary stirring: Mix large-size regenerated sand and corresponding amount of water for 30 seconds; (2) Second stirring: then add part of the slag and stir for 60 seconds; (3) Third mixing: Add cement and remaining slag and mix for 60 seconds; (4) Fourth mixing: Add small-size regenerated sand, remaining water and water reducer, stir for 60 seconds to form a uniform regenerated mortar mixture, and cast the test block.
[0032] The material ratio is as follows: Cement: 191 kg / m³ Slag: 191 kg / m³ (153 kg / m³ in the first part, 38 kg / m³ in the second part) Regenerated sand: 1147 kg / m³ (large particle size 803 kg / m³, small particle size 344 kg / m³) Water: 382 kg / m³ (125 kg / m³ in the first part, 257 kg / m³ in the second part) Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 5.26 MPa and 4.94 MPa, respectively, and the compressive strength is 20.21 MPa and 17.50 MPa, respectively. The results show that the mortar prepared by the method of the present invention is 6.49% higher in flexural strength and 15.49% higher in compressive strength than the conventional method.
[0033] Example 3 Reference Figure 2 A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: First, the reclaimed sand is divided into two main parts according to the particle size: a large particle size part larger than 0.63 mm and a small particle size part smaller than 0.63 mm.
[0034] (II) Staged stirring process: (1) Primary stirring: Mix large-size regenerated sand and corresponding amount of water for 30 seconds; (2) Second stirring: then add part of the slag and stir for 60 seconds; (3) Secondary mixing: Add cement and remaining slag and mix for 60 seconds; (4) Three-stage mixing: Add small-size regenerated sand, remaining water and water reducer, stir for 60 seconds to form a uniform regenerated mortar mixture, and cast the test block.
[0035] The material ratio is as follows: Cement: 210 kg / m³ Slag: 210 kg / m³ (42 kg / m³ in the first part, 168 kg / m³ in the second part) Regenerated sand: 1259 kg / m³ (large particle size 881 kg / m³, small particle size 378 kg / m³) Water: 336 kg / m³ (138 kg / m³ in the first part, 198 kg / m³ in the second part) Water reducing agent: 2.9 kg / m³ Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 7.54 MPa and 6.50 MPa, respectively, and the compressive strength is 46.11 MPa and 41.71 MPa, respectively. The results show that the mortar prepared by the method of the present invention is 16.00% higher in flexural strength and 10.55% higher in compressive strength than the conventional method.
[0036] Example 4 Reference Figure 2A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: In this embodiment, the regenerated sand is first divided into two main parts according to the particle size: a large particle size part greater than 1.25 mm and a small particle size part less than 1.25 mm.
[0037] (II) Staged stirring process: (1) Primary stirring: Mix large-size regenerated sand and corresponding amount of water for 30 seconds; (2) Second stirring: then add part of the slag and stir for 60 seconds; (3) Third mixing: Add cement and remaining slag and mix for 60 seconds; (4) Fourth mixing: Add small-size regenerated sand, remaining water and water reducer, stir for 60 seconds to form a uniform regenerated mortar mixture, and cast the test block.
[0038] The material ratio is as follows: Cement: 399.6 kg / m³ Slag: 44.4 kg / m³ (22.2 kg / m³ in the first part, 22.2 kg / m³ in the second part) Regenerated sand: 1334 kg / m³ (large particle size 760 kg / m³, small particle size 574 kg / m³) Water: 311 kg / m³ (118 kg / m³ in the first part, 139 kg / m³ in the second part) Water reducing agent: 1.1 kg / m³ Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 8.7 MPa and 8.00 MPa, respectively, and the compressive strength is 52.60 MPa and 47.31 MPa, respectively. The results show that the mortar prepared by the method of the present invention is 8.75% higher in flexural strength and 11.18% higher in compressive strength than the conventional method.
[0039] Example 5 Reference Figure 2 A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: In this embodiment, the regenerated sand is first divided into two main parts according to the particle size: a large particle size part greater than 1.25 mm and a small particle size part less than 1.25 mm.
[0040] (II) Staged stirring process: (1) Primary stirring: Mix the large-size regenerated sand and the corresponding amount of water (the amount of water added is 1.2 times the water absorption rate of the large-size regenerated sand) and stir for 30 seconds; (2) Second stirring: then add part of the slag and stir for 60 seconds; (3) Third mixing: Add cement and remaining slag and mix for 60 seconds; (4) Fourth mixing: Add small-size regenerated sand, remaining water and water reducer, stir for 60 seconds to form a uniform regenerated mortar mixture, and cast the test block.
[0041] The material ratio is as follows: Cement: 355.2 kg / m³ Slag: 88.8 kg / m³ (44.4 kg / m³ in the first part, 44.4 kg / m³ in the second part) Regenerated sand: 1334 kg / m³ (large particle size 760 kg / m³, small particle size 574 kg / m³) Water: 311 kg / m³ (118 kg / m³ in the first part, 139 kg / m³ in the second part) Water reducing agent: 1.1 kg / m³ Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 8.30MPa and 8.07MPa, respectively, and the compressive strength is 59.05MPa and 51.59MPa, respectively. The results show that the mortar prepared by the method of the present invention is 2.85% higher in flexural strength and 14.46% higher in compressive strength than the conventional method.
[0042] Example 6 Reference Figure 2 A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: In this embodiment, the regenerated sand is first divided into two main parts according to the particle size: a large particle size part greater than 1.25 mm and a small particle size part less than 1.25 mm.
[0043] (II) Staged stirring process: (1) Primary stirring: Mix large-size regenerated sand and corresponding amount of water for 30 seconds; (2) Second stirring: then add part of the slag and stir for 60 seconds; (3) Third mixing: Add cement and remaining slag and mix for 60 seconds; (4) Fourth mixing: Add small-size regenerated sand, remaining water and water reducer, stir for 60 seconds to form a uniform regenerated mortar mixture, and cast the test block.
[0044] The material ratio is as follows: Cement: 222 kg / m³ Slag: 222 kg / m³ (44.4 kg / m³ in the first part, 177.6 kg / m³ in the second part) Regenerated sand: 1334 kg / m³ (large particle size 760 kg / m³, small particle size 574 kg / m³) Water: 311 kg / m³ (118 kg / m³ in the first part, 139 kg / m³ in the second part) Water reducing agent: 1.1 kg / m³ Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 8.29 MPa and 7.68 MPa, respectively, and the compressive strength is 54.96 MPa and 46.19 MPa, respectively. The results show that the mortar prepared by the method of the present invention is 7.94% higher in flexural strength and 18.99% higher in compressive strength than the conventional method.
[0045] Example 7 Reference Figure 2 A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: First, the reclaimed sand is divided into two main parts according to the particle size: a large particle size part larger than 0.63 mm and a small particle size part smaller than 0.63 mm.
[0046] (II) Staged stirring process: (1) Primary stirring: Mix large-size regenerated sand and corresponding amount of water for 30 seconds; (2) Second stirring: then add part of the slag and stir for 60 seconds; (3) Third mixing: Add cement and remaining slag and mix for 60 seconds; (4) Fourth mixing: Add small-size regenerated sand, remaining water and water reducer, stir for 60 seconds to form a uniform regenerated mortar mixture, and cast the test block.
[0047] The material ratio is as follows: Cement: 266.4 kg / m³ Slag: 177.6 kg / m³ (88.8 kg / m³ in the first part, 88.8 kg / m³ in the second part) Regenerated sand: 1334 kg / m³ (large particle size 934 kg / m³, small particle size 400 kg / m³) Water: 311 kg / m³ (146 kg / m³ in the first part, 165 kg / m³ in the second part) Water reducing agent: 5.6 kg / m³ Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 8.56 MPa and 7.98 MPa, respectively, and the compressive strength is 56.91 MPa and 51.55 MPa, respectively. The results show that the mortar prepared by the method of the present invention is 7.27% higher in flexural strength and 10.40% higher in compressive strength than the conventional method.
[0048] Example 8 Reference Figure 2 A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: First, the reclaimed sand is divided into two main parts according to the particle size: a large particle size part larger than 0.63 mm and a small particle size part smaller than 0.63 mm.
[0049] (II) Staged stirring process: (1) Primary stirring: Mix large-size regenerated sand and corresponding amount of water for 30 seconds; (2) Second stirring: then add part of the slag and stir for 60 seconds; (3) Third mixing: Add cement and remaining slag and mix for 60 seconds; (4) Fourth mixing: Add small-size regenerated sand, remaining water and water reducer, stir for 60 seconds to form a uniform regenerated mortar mixture, and cast the test block.
[0050] The material ratio is as follows: Cement: 222 kg / m³ Slag: 222 kg / m³ (44.4 kg / m³ in the first part, 177.6 kg / m³ in the second part) Regenerated sand: 1334 kg / m³ (large particle size 934 kg / m³, small particle size 400 kg / m³) Water: 311 kg / m³ (146 kg / m³ in the first part, 165 kg / m³ in the second part) Water reducing agent: 5.6 kg / m³ Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 8.11 MPa and 7.68 MPa, respectively, and the compressive strength is 52.29 MPa and 46.19 MPa, respectively. The results show that the mortar prepared by the method of the present invention is 5.60% higher in flexural strength and 13.21% higher in compressive strength than the conventional method.
[0051] Example 9 Reference Figure 2A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: First, the reclaimed sand is divided into two main parts according to the particle size: a large particle size part larger than 2.50 mm and a small particle size part smaller than 2.50 mm.
[0052] (II) Staged stirring process: (1) Primary stirring: Mix large-size regenerated sand and corresponding amount of water for 30 seconds; (2) Second stirring: then add part of the slag and stir for 60 seconds; (3) Third mixing: Add cement and remaining slag and mix for 60 seconds; (4) Fourth mixing: Add small-size regenerated sand, remaining water and water reducer, stir for 60 seconds to form a uniform regenerated mortar mixture, and cast the test block.
[0053] The material ratio is as follows: Cement: 222 kg / m³ Slag: 222 kg / m³ (88.8 kg / m³ in the first part, 133.2 kg / m³ in the second part) Regenerated sand: 1334 kg / m³ (large particle size 600 kg / m³, small particle size 734 kg / m³) Water: 311 kg / m³ (79 kg / m³ in the first part, 232 kg / m³ in the second part) Water reducing agent: 5.6 kg / m³ Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 8.05 MPa and 7.68 MPa, respectively, and the compressive strength is 46.54 MPa and 46.19 MPa, respectively. The results show that the mortar prepared by the method of the present invention is 4.82% higher in flexural strength and 0.76% higher in compressive strength than the conventional method.
[0054] Example 10 Reference Figure 2 A method for strengthening slag cement-based recycled mortar is carried out according to the following steps: (I) Accurate classification: First, the regenerated sand is divided into two main parts according to the particle size: a large particle size part larger than 0.315 mm and a small particle size part smaller than 0.315 mm.
[0055] (II) Staged stirring process: (1) Primary stirring: Mix large-size regenerated sand and corresponding amount of water for 30 seconds; (2) Second stirring: then add part of the slag and stir for 60 seconds; (3) Third mixing: Add cement and remaining slag and mix for 60 seconds; (4) Fourth mixing: Add small-size regenerated sand, remaining water and water reducer, stir for 60 seconds to form a uniform regenerated mortar mixture, and cast the test block.
[0056] The material ratio is as follows: Cement: 222 kg / m³ Slag: 222 kg / m³ (88.8 kg / m³ in the first part, 133.2 kg / m³ in the second part) Regenerated sand: 1334 kg / m³ (large particle size 1040 kg / m³, small particle size 294 kg / m³) Water: 311 kg / m³ (187 kg / m³ in the first part, 124 kg / m³ in the second part) Water reducing agent: 5.6 kg / m³ Performance comparison analysis: The flexural strength of the slag cement-based recycled mortar prepared by the mixing process of the present invention and the slag cement-based recycled mortar prepared by the conventional mixing method are 7.78 MPa and 7.68 MPa, respectively, and the compressive strength are 47.20 MPa and 46.19 MPa, respectively. The results show that the mortar prepared by the method of the present invention is 1.30% higher in flexural strength and 2.19% higher in compressive strength than the conventional method.
[0057] The above specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A method for strengthening slag cement-based recycled mortar, characterized in that The steps include: (I) Fine grading: The regenerated sand is divided into two parts according to the particle size: large particle size and small particle size, and the particle size cutoff point is set at 0.63-2.50 mm; (II) Stirring in stages: (1) Primary mixing: Mix large-size regenerated sand and water for 25 to 55 seconds; (2) Secondary stirring: Then add part of the slag and stir for 40 to 70 seconds; (3) Third mixing: Add cement and remaining slag and mix for 40 to 70 seconds; (4) Fourth mixing: add small-size regenerated sand, remaining water and water reducer, stir for 40 to 70 seconds to form a uniform regenerated mortar mixture, and cast the test block; Among them, the mass ratio of cement, slag, regenerated sand, water and water reducing agent is 0.1-0.9: 0.1-0.9: 2.0-4.0: 0.7-1.1: 0-0.0125.
2. The method for strengthening slag cement-based regenerated mortar according to claim 1, characterized in that: The particle size cutoff point was set at 0.63 mm.
3. The method for strengthening slag cement-based regenerated mortar according to claim 1, characterized in that: The particle size cutoff point was set at 1.25 mm.
4. The method for strengthening slag cement-based regenerated mortar according to claim 1, characterized in that: The first stirring time is 30 seconds, the second stirring time is 60 seconds, the third stirring time is 60 seconds, and the fourth stirring time is 60 seconds.
5. The method for strengthening slag cement-based regenerated mortar according to claim 1, characterized in that: The water reducing agent is a polycarboxylate ether type water reducing agent.
6. The method for strengthening slag cement-based regenerated mortar according to claim 1, characterized in that: The slag is added in batches, and the mass ratio of the slag added for the first time to the slag added for the second time is 1:0-6.
7. The method for strengthening slag cement-based regenerated mortar according to claim 1, characterized in that: The mass ratio of the water added for the first time to the water added for the second time is 1:1-4.
Citation Information
Patent Citations
Low-carbon reclaimed sand concrete and preparation method thereof
CN118619630A
Waste glass fiber reinforced plastic mortar pipe broken material recycled mortar and preparation method thereof
CN118878266A